Long-term stellar variability in the Galactic Centre region. Issue 4 (10th November 2018) - Molina, C N; Borissova, J; Catelan, M; Lucas, P W; Medina, N; Contreras Peña, C; Kurtev, R; Minniti, D
ABSTRACT: We report the detection of variable stars within a$11.5\, \text{arcmin}× 11.5\, \text{arcmin}$ region near the Galactic Centre that includes the Arches and Quintuplet clusters, as revealed by the VISTA Variables in the Vía Láctea survey. There are 353 sources that show K S -band variability, of which the large majority (81 per cent) correspond to red giant stars, mostly in the asymptotic giant branch phase. We analyse a population of 52 red giants with long-term trends that cannot be classified into the typical pulsating star categories. Distances and extinctions are calculated for nine Mira variables, and we discuss the impact of the chosen extinction law on the derived distances. We also report the presence of 48 new identified young stellar object candidates in the region.